Evaluation of sodium percarbonate as a bath treatment for amoebic gill disease in Atlantic salmon. (9th September 2020) - Taylor, Richard S.; Slinger, Joel; Camargo Lima, Paula; English, Chloe J.; Maynard, Ben T.; Samsing, Francisca; McCulloch, Russell; Quezada‐Rodriguez, Petra R.; Wynne, James W.
Abstract: Amoebic gill disease (AGD), caused by Neoparamoeba perurans, is a major health challenge for Atlantic salmon aquaculture globally. While freshwater bathing for 2 hr is effective in reducing infection severity, there is need for more rapid and lower cost alternatives. To this end, a combination of sodium percarbonate (SPC) in freshwater was examined for its treatment efficacy. Initial in vitro studies showed a reduction in amoeba viability when exposed for 30 min to freshwater containing >500 mg/L SPC. Subsequently, AGD‐affected salmon were bathed for 30 min in 16°C freshwater containing 100, 500 or 1, 000 mg/L SPC, or for 2 hr in 16°C freshwater to mimic industry practice. Treatment at the highest SPC concentration caused extensive gill damage and substantial mortality. Neither occurred to a significant extent at lower SPC concentrations. Gill pathology of surviving fish 10 days post‐treatment (dpt) was comparable to or more severe than pre‐treatment, and significantly ( p < .001) more severe than in 2 hr freshwater bathed fish. N. perurans DNA was confirmed by qPCR in all treatment groups at 10 dpt. The data indicate that a 30‐min exposure to SPC in freshwater is not a suitable alternative to existing freshwater treatment of AGD.